Tree reconstruction using energy aware sink mobility to prolong network lifetime in WSN. (8th May 2021) - Kumar, Hemanth; Nagarjun, E.; Kumar, S.M. Dilip
Sensor nodes residing near a sink receives more traffic than other nodes and depletes their battery quickly which leads to an energy hole problem. The objective is to collect data from all over the sensor field, aggregate and forward the same to a mobile sink to extend the network lifetime. A sensor network is logically divided into subgrids and each is identified uniquely and the sink is aware of the number of sensors under each subgrid. During data collection, a mobile sink move towards a potential subgrid so that the energy of all the sensor nodes is equally utilised. It is implemented through reconstructing the network and new routing paths are generated. The sink moves to a new subgrid where sensor nodes have adequate residual energy and starts collecting data, which prolongs the network lifetime. Parameters like average lifetime of nodes, packet delivery ratio and throughput of the network are considered for performance analysis. Residual energy obtained from the simulation shows that the lifetime of the network is improved.